Conversations on Violence in India - Sen, Ronojoy (Pacific Affairs, 2024)
This essay briefly discusses accounts of violence in India before reviewing three recent books that examine the place of violence in Indian political thought. All three books provide insights into the minds of some of the thinkers who have shaped modern India. While two of the authors focus on Mahatma Gandhi and V. D. Savarkar, respectively, the third is more wide-ranging in focus. All three books are important contributions to the study of violence in India, but also a reminder that India's founding figures remain the objects of contestation and appropriation by political parties and movements.
Keywords: Gita; Hinduism; Savarkar; Violence in India; Hindutva